Pemanfaatan Limbah Plastik Polypropylene (PP) Sebagai Bahan Baku Pembuatan Ecological Bricks Dengan Kalsium Karbonat Sebagai Admixture - R. Rindu Permatasari; David Andrio; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The country of Indonesia is currently published as the second largest contributor of plastic waste in the world, amounting to 28.4 thousand tons of plastic waste / day. Plastic has caused problems in the environment and become waste that is difficult to be reprocessed. Ecobricks (environmentally friendly brick) are made from plastic waste so that it can reduce environmental pollution caused by garbage so as to minimize the generation of plastic waste and prevent air from arising from the process of making ecobricks without having to go through surgery. This study discusses polypropylene (PP) glass packaging and refined aggregate containing carbonate mixtures with a variation of 5%, 7% and on the compressive strength and movement of concrete water according to PUBI, 1982. From the results of the research, the highest compressive strength of the concrete block with PP plastic mixture and 5% carbonate mixture at 28 days is 93 kg / cm2 . Batako at the time of 28 days, the highest absorption of air (absorption) occurred in a normal brick that is 14 66%.Keywords: ecobricks, polypropylene (PP), calcium carbonate, compressive strength, absorbtion